Proton Plasma Bulk-Parameter Measurements in Venus' Dayside Magnetosheath - Rojas Mata, Sebastián; Futaana, Yoshifumi (Swedish Institute of Space Physics, 2023)
This is a high-level data product based on particle and magnetic-field measurements taken by the Ion Mass Analyser (IMA) and Magnetometer (MAG) instruments, respectively, onboard the European Space Agency’s (ESA’s) Venus Express (VEX) mission. VEX orbited Venus between 2006-2014 collecting data on the plasma environment around the planet for a wide variety of space physics studies. IMA is an ion mass-energy spectrometer from which plasma bulk parameters can be calculated. MAG measures the three components of the background magnetic field.

The dataset contains proton bulk densities, speeds, and temperatures (perpendicular and parallel to the magnetic field) measured by IMA at 1181 spatial locations in Venus’ dayside magnetosheath. The concurrent average magnetic-field strength measured by MAG accompanies each set of proton parameters. Additionally, medians of the same parameters measured in the upstream solar wind (SW) during each orbit are included (but not the individual measurements from which the medians are calculated). The location of VEX during each measurement is provided in the Venus Solar Orbit (VSO) reference frame along with the timestamp for the measurement and the corresponding VEX orbit number.

The proton parameters were calculated through Maxwellian fits of velocity-distribution-function (VDF) measurements derived from IMA’s scans of particle counts over a mass-energy-azimuth-elevation parameter space. This methodology was developed by Bader et al. (2019) and applied to data between 2006-2009; Rojas Mata et al. (2022) extended it to process the entire mission data. The data included in this product form the basis for studies concerning asymmetries in the parameters between different hemispheres of Venus’ magnetosheath. The manually selected orbits have adequate coverage in the magnetosheath and SW as well as sufficiently stable SW conditions to lead to statistically reliable results. This therefore is a subset of the entire mission data (597 orbits out of ~3200 total orbits).

Dataprodukten innehåller bearbetade data från joninstrumentet Ion Mass Analyser (IMA) och magnetometern MAG på rymdfarkosten Venus Express. Under 2006-2014 observerade dessa instrument jonegenskaper och magnetfält i Venus plasmamiljö. I dataprodukten ingår uppmätta egenskaper för protoner på 1181 platser i magnetoskiktet samt motsvarande median-värden för solvindparametrarna under 597 banor. Datat används i en studie om plasmaasymmetrier där vi jämför olika Venus hemisfärer. För ytterligare information hänvisar vi till beskrivningen på engelska.
Proton Plasma Bulk-Parameter Measurements in Venus' Dayside Magnetosheath
Keywords: space plasma physics; rymdplasmafysik; ion spectrometers; space plasmas; venus (planet); Venus Express; Venus Express; Fusion, Plasma and Space Physics; Fusion, plasma och rymdfysik